WAYS TO DEVELOP CREATIVE THINKING OF PRIMARY SCHOOL STUDENTS USING INTERNATIONAL ASSESSMENT PROGRAMS AND NEW GENERATION TEXTBOOKS - Abdullaev Gulmira Abdullayevna (Scholar Express Journal, 2023)
We know that it is necessary to attract best practices to improve the quality of education by evaluating and monitoring the development of education and science. This article discusses the international system for assessing the quality of education, international experience in determining, analyzing and implementing the quality of primary education, the role and importance of foreign research in determining the priorities of the national education system and participation in international studies of methods for assessing the quality of primary education.
Keywords: PISA; TIMSS; TALIS; PIRLS